DEVELOPMENT OF MEDICINAL VEGETABLE CULTIVATION FOR FAMILY USE (TOSGA) IN REALIZING SUSTAINABLE AGRICULTURAL INNOVATION FOR WOMEN IN PENGABUAN VILLAGE, ABAB DISTRICT, PALI REGENCY, SOUTH SUMATRA - Sarion Masona; Adam S. Nasution; Erwin Hendra Putra (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2024)
In Pengabuan Village, women dominate poverty. The vulnerability of this group is explained by the fact that they do not have enough training, experience, and a source of investment to put food on their table (to meet even basic family needs, including healthcare). This journal in this case study is the implementation of the Independent Agriculture for Empowerment Village Women ("PERMATA") program, which is initiated by PT Pertamina EP Adera Field at Pengabuan Village, Abab Districts, Penukal Abab Lematang Ilir (PALI), South Sumatera. Its purpose is to increase economic welfare as well as the health of society by growing Medicinal Family Vegetables (TOSGA). Under the theme of building an inclusive and sustainable economy, PERMATA, in its fourth year, will focus on product diversification from TOSGA-derived herbs and group capacity building, followed by institutional mentoring. The program has had far-reaching effects on economic, social, and environmental welfare. One initiative has seen a dramatic increase in the income of women's groups and made a real dent in greenhouse gas emission targets through straw waste alternative energy. The PERMATA program has increased community awareness and capabilities in managing the environment and the production of herbs as flora medicinal plants. Through sustainable agricultural innovation, the program also improved quality life criteria or indicators of life.